Case Study of Teacher Leadership Style to Improve Junior High School Student Discipline - Sri Untari, Rahmania; Dilara, Aliya Farah; Masfufah, Ayu Nikmatul (Universitas Muhammadiyah Sidoarjo, 2024)
Learning activities are a form of a series of behaviors between teachers and students in the classroom in achieving learning goals. Among the forms of student management in the classroom is to discipline students. Behavior influencing teachers towards students is a form of teacher leadership over students. Based on the results of the study, it is known that: (1) teachers of junior high school science subjects in Sidoarjo use situational leadership styles, and (2) the formulation of teacher leadership efforts in improving student discipline, namely, (a) the intention to change the undisciplined attitude of students, (b) be firm with students, (c) discipline students with a non-violent heart, (d) students who are not disciplined are punished in a gentle and educational way, (e) providing treatment to students according to the attitude and behavior of each student, (f) students are accustomed to smiling and shaking hands with their teachers when entering the classroom, (g) when students are late students are not allowed to enter the classroom but are still punished in an educational way, and (h) students who are late to class and do not do their assignments are reduced every day.